2023
DOI: 10.1177/15579883231181861
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Bacteriospermia on Semen Parameters Among Infertile Egyptian Men: A Case–Control Study

Rania Yahia Mohammad Shash,
Gehad Attia Abdallah Mohamed,
Salah E. Shebl
et al.

Abstract: This study aimed to detect the impact of bacteriospermia on semen parameters and sperm DNA fragmentation. This prospective case–control study was conducted over a period of 9 months. Samples were collected from andrology outpatient clinic attendants of Cairo University Hospitals. We enrolled 68 semen samples divided into two groups: a study group (34 semen samples with bacteriospermia) and a control group (34 semen samples without bacteriospermia). The characteristics of the semen, including morphology, motili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…However, it has been shown that ejaculate is normally populated by commensals such as Staphylococcus epidermidis or S. viridans and/or contaminated with bacteria of the anterior urethra [82,83]. Although there are numerous reports [35][36][37][38][39][40] about the clinical relevance of the bacterial contamination of semen and the fact that a semen sample is considered "significant" bacteriospermic if the semen culture shows more than 10 3 colony-forming units (cfu)/mL [41,84], the WHO does not mention the term in their two latest manuals for semen analysis [42,43], which might be for various reasons. On the other hand, E. coli and E. faecalis are regarded as pathogens and causes of about 90% of chronic bacterial prostatitis cases (NIH II) [41,85].…”
Section: Prevalence Of Bacteriospermiamentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has been shown that ejaculate is normally populated by commensals such as Staphylococcus epidermidis or S. viridans and/or contaminated with bacteria of the anterior urethra [82,83]. Although there are numerous reports [35][36][37][38][39][40] about the clinical relevance of the bacterial contamination of semen and the fact that a semen sample is considered "significant" bacteriospermic if the semen culture shows more than 10 3 colony-forming units (cfu)/mL [41,84], the WHO does not mention the term in their two latest manuals for semen analysis [42,43], which might be for various reasons. On the other hand, E. coli and E. faecalis are regarded as pathogens and causes of about 90% of chronic bacterial prostatitis cases (NIH II) [41,85].…”
Section: Prevalence Of Bacteriospermiamentioning
confidence: 99%
“…Therefore, bacteriospermia, which is defined as the presence of bacteria in seminal fluid [34], is thought to negatively impact male fertility. Although there are numerous reports [35][36][37][38][39][40] about the clinical relevance of the bacterial contamination of semen and the fact that a semen sample is considered bacteriospermic if the semen culture shows more than 10 3 colony-forming units (cfu)/mL [41], the World Health Organization (WHO) does not mention the term in their two latest manuals for semen analysis [42,43], which might be for various reasons. Therefore, the aim of this narrative review is to provide an update on the current knowledge on leukocytospermia and bacteriospermia and their impact on male fertility.…”
Section: Introductionmentioning
confidence: 99%
“…However, it remains to understand the complex and multifaceted molecular foundations that underpin the quality of semen associated with bacteriospermia [4]. Bacteriospermia is associated with increased DNA level fragmentation of sperm and negative effects on sperm characteristics such as motility and morphology [5]. Although the precise mechanisms by which bacterial species cause these harmful effects are unknown, it is assumed that they can cause oxidative stress (OS), inflammation, and other pathogenic processes in the male reproductive tract [6].…”
Section: Introductionmentioning
confidence: 99%